Annex IV Marine Pollution (MARPOL) Application for Pollution Prevention on Ketapang-Gilimanuk Route Crossing Vessels with Analytical Hierarchy Process (AHP) Method - Hadi, Agung Pangestu; Kisnarti, Engki Andri; Sugianto, Erik (Institut Teknologi Sepuluh Nopember, 2024)
The Application of the Marine Pollution (MARPOL) Annex IV regulation concerning sewage discharge from ferry ships operating on the Ketapang-Gilimanuk route plays a crucial role in pollution prevention. However, this essential role has been compromised due to suspicions that sewage waste from the Ketapang-Gilimanuk ferry ships is being directly discharged into the sea. Additionally, it is believed that the lack of sewage storage facilities at the port and inadequate supervision by local port authorities contribute to this issue. This research aims to investigate the implementation of MARPOL Annex IV in pollution prevention on ferry ships along the Ketapang – Gilimanuk route using the Analytical Hierarchy Process (AHP) method. This method is employed to establish a comprehensive evaluation framework by considering criteria such as safety management systems, safety and environmental protection policies, Company responsibilities and authorities, cultural and behavioral aspects, organizational factors, and technical considerations. Data will be collected through surveys and interviews with ship operators and members. Economical is more priority than operational techniques because it is related to capital expenditure and operational costs of each alternative to prevent marine pollution. Operational techniques are more priority than safety and environment because they are related to the technical and operational of each alternative to preventing marine pollution. Regulations are more priority than safety and environment because regulations affect each alternative, both Indonesian regulations and also SOPs at ports.